2012 IEEE 36th Annual Computer Software and Applications Conference Workshops 2012
DOI: 10.1109/compsacw.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Software Service Evolution: A Requirements Perspective

Abstract: Abstract-Software service has to adapt to constant changes of requirements and environment, which would give rise to the concentration on service evolution. Among the many reasons for evolution, requirements are regarded as the major driving factor. However, most current work on service evolution focuses on different kinds of tactics to keep the compatibility between services and client applications, few of them treat requirements in priority. In this paper, we thoroughly survey the state-of-the-art studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The software employed the Linux system as the operating system. And the Linux system has these advantages: (1)The sound codes of the inner core are totally open, and it has favorable tailing capability and customizability. (2)The Linux system can support the microprocessor broadly.…”
Section: The Design Of the Terminal Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…The software employed the Linux system as the operating system. And the Linux system has these advantages: (1)The sound codes of the inner core are totally open, and it has favorable tailing capability and customizability. (2)The Linux system can support the microprocessor broadly.…”
Section: The Design Of the Terminal Softwarementioning
confidence: 99%
“…But when the signal of the GPS is weak, the terminal won't work well. And also in the area where the wireless communication signals are weak or not available, the terminal will not be able to transmit the information to the center, and the control center can't control and dispatch the vehicles [1]. In order to solve this problem, we designed an intelligence terminal in motorbus which employed the GPS combined with BD2.…”
Section: Introductionmentioning
confidence: 99%
“…In software service evolution, the well-known challenge is to keep the compatibility between evolved service and existing client applications at either structural [7] or behavior level [8] [9]. Through our extensive survey [10], we found that starting from the definition of service evolution given by M. Papazoglou [9], many efforts have committed themselves to solve the problem by using kinds of tactics, such as versioning, design pattern/adaptor, model and theory [7], but few of them paid enough attention to the change propagation from requirements to services, one of the fundamental problem of evolution.…”
Section: Related Workmentioning
confidence: 99%